Food Neophobia and Willingness to Try Plant - Based Meat in Bangkok - Monta, Nahathai; Sayruamyat, Suwanna; Premashthira, Aerwadee (Journal of Business, Innovation and Sustainability (JBIS), 2022)
This article aims to explore food neophobia and consumers’ willingness to try the product of plant-based meat (PBM). 232 responses were collected via questionnaires. The results demonstrate that the 196 responses (84.4 percent) who are willing to try PBM have a lower food neophobia score (2.3 score) than respondents who were not willing to try the product (3.8 score) Food neophobia effects consumer decision and the group with lower score have higher intention to try PBM. Two-Step Cluster Analysis separates respondents into 4 groups: Meat Lover, Pork Lover, Beef Lover and Red Meat Lover. Meat Lover is not willing to try PBM while other groups reject it. The results indicates that there are consumers interested in and willing to try PBM products. Thus, food entrepreneurs should add PBM menu. It will be an alternative dish for customer and increase profits for food entrepreneurs and the producer should use this data to develop marketing strategies focusing on the group who have willingness to try PBM products.